A APLICAÇÃO DA GESTÃO POR PROCESSOS EM UMA ORGANIZAÇÃO HOSPITALAR: UM ESTUDO DE CASO NO HOSPITAL JORGE VALENTE, SALVADOR-BA - Grijó, Fabíola Azevedo (2010)
Process Management, which is used in organizations from many different industries, is a system or organizational administration model designed for managing an organization focusing on processes, enabling an horizontal, systemic and integrated structure. This paper focus on analyzing the Process Management in a hospital organization and more specifically on understanding and featuring the application of Process Management in a hospital. The methodological strategy is divided in two steps: theoretical approach based on bibliographic research and an empiric study that has the Jorge Valente Hospital, in Salvador, Bahia, as subject; the methodology for studying this case is based on document research and personal interviews. It is possible to assess that applying and using Process Management involved not only Jorge Valente Hospital's senior executives, but also leaders and professionals from several hierarchical levels. In the case study it was observed the application of Process Management at Jorge Valente Hospital through indicators presented and validated by the staff. It was highlighted relevant aspects for the administration, e.g.: decentralization, advancements in leadership, hierarchy horizontalization, participative management and improvements for the patients.